(untitled) (Journal of Education and Development, 2023)
In recent years, there has been a promotion and emphasis on CLIL (Content and Language Integrated Learning) and STEAM (Science, Technology, Engineering, Arts, and Mathematics) education. The integration of interdisciplinary concepts and applications in English classrooms has brought new value and significance to English teaching. This study aims to investigate the students’ perceptions by STEAM-Integrated CLIL instruction into English Classroom, a Halloween Jack-O-Lantern as an example. The participations were eight freshman students from different department in a university in central of Taiwan. Through a survey, the research aims to analyze different aspects of STEAM and assess the effectiveness of English learning outcomes. The results indicated that the students were satisfied with the application of STEAM education in CLIL instruction in English classroom.